Space Is Set in Motion (KULT_online, 2010)
The volume Raum und Bewegung in der Literatur. Die Literaturwissenschaften und der Spatial Turn (Space and Movement in Literature: Literary Studies and the Spatial Turn), edited by Wolfgang Hallet and Birgit Neumann in 2009, discusses in an introduction and eighteen articles new horizons in the literary representation of space and movement after the spatial turn. With contributions from literary and theatre studies, this highly constructive volume focuses on theoretical concepts of space in literature, on the perception of space and on some genre-specific questions in order to give a broad overview of the field.